Efficacy of duodenum-preserving pancreatic head resection versus pancreaticoduodenectomy in the treatment of chronic pancreatitis in adults: Systematic Review and Meta-Analysis - Silva-Santisteban Gálvez, Sergio (2022)
Background: Studies comparing duodenum-preserving pancreatic head resection versus pancreaticoduodenectomy in the treatment of chronic pancreatitis demonstrate notable differences, however, the current evidence is inadequate to clearly establish the superiority of these approaches. Objective: To determine duodenum preserving pancreatic head resection is more effective than pancreaticoduodenectomy in treating chronic pancreatitis in adults. Material and Methods: A systematic review was conducted identifying and extracting data from seven randomized clinical trials and seven observational studies comparing the efficacy of duodenum-preserving pancreatic resection versus pancreaticoduodenectomy. Results: Bleeding had a mean difference (MD) of -0.18, 95% CI of -0.25 – -0.12, and p < 0.00001. Operative time had an MD of -1.32, 95% CI of -2.20 –      -0.44 and p = 0.003. Hospital stay had an MD of -3.94, 95% CI of -6.16 – -1.71 and p = 0.0005. Endocrine insufficiency had a RR of 0.78, 95% CI of 0.65 – 0.95 and p = 0.01. Pain Score showed an MD of -7.39, 95% CI of -13.05 – -1.74 and p = 0.01. Global quality of life, showed MD of 8.97, 95% CI of 4.05 - 13.90 and p = 0.0004. Conclusions: DPPHR is more effective than PD by reducing intraoperative bleeding, operative time, hospital stay, the risk of endocrine failure, and by providing better pain relief and quality of life.